Ultrastructure of the synganglion in the larvae and nymphs of tick Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Roma, Gislaine Cristina [UNESP]; Camargo Mathias, Maria Izabel [UNESP]; Nunes, Pablo Henrique [UNESP]; Bechara, Gervasio Henrique [UNESP] (Taylor & Francis Inc, 2014)
This study performs the ultrastructural description of the central nervous system (CNS) of Rhipicephalus sanguineus larvae and nymphs. The CNS is surrounded by the neural lamella, a thin acellular sheath. Just below, the perineurium is found, formed by glial cells, with irregular membranes, elongated nucleus and few organelles in the cytoplasm. Internally, the synganglion is divided into an outer cortex, containing the cellular bodies of the neural cells and an inner neuropile. The neural cells can be classified into two types. Type I is most frequently observed, presenting spherical or oval shape and a large nucleus occupying most part of the cytoplasm, in which few organelles are observed. Type II cells are polygonal, presenting a great cytoplasmic volume and the nucleus dislocated towards the cellular periphery. The subperineurium is located between the cortex and the neuropile. The neuropile is the innermost region of the synganglion, the most complex one and formed by extensions of the neural cells. This study improves our understanding of the physiology of ticks, with the aim of improving current control strategies.
Keywords: brown dog tick; immature stages; central nervous system; synganglion; ultrastructure